Accessibility to Public Health Centres: The Case of the Urban and Rural Poor in Delta State, Nigeria - Abotutu Ahi Abel (Archives of Current Research International, 2015)
For any nation to develop, three things are very critical and important; education, health and food. Citizens, particularly the workforce must be educated, healthy and well fed. If the workforce lacks any of the three, they cannot be competitive and if they are not, the country cannot develop. This realization provides the impetus for this study which aims to investigate poor users access to public health centres in Delta State, Nigeria. The sampling design adopted include a multistage sampling at two stages: first, a random sampling of public health centres and second, a stratified random sampling of 700 patients to solicit their responses on the service accessibility of public health centres in their environment. The questionnaire content was based on thirteen (13) independent variables namely: travel distance, educational status, sex, age, household size, travel cost, treatment cost, travel mode, travel time, waiting time, income, religion and perceived efficiency of public health centre services. Analysis of data was done using Multiple regression, Principal component analysis and Nearest Neighbour Analysis (NNA) as statistical tools. The coefficient of determination (R2) = 0.972, confirmed that 97.2% of access to public health centres in the study area is explained by the selected independent variables. The principal component analysis showed that the four (4) most important predictor variables of service accessibility include – travel distance, travel time, waiting time and income. The study recommends re-distribution of mal-distributed public health centres in tandem with physical planning principles to minimize travel distance to public health centres and the provision of ambulatory services to reduce travel time for users of public health centres.